The Effect of Job Satisfaction and Personality on Organizational Citizenship Behavior through Organizational Commitment - Isyah, Khusnul Ma; Palupiningdyah, Palupiningdyah (Management Analysis Journal, 2020)
This study aims to examine the effect of job satisfaction and personality on organizational citizenship behavior through the organizational commitment of employees in the production section of PT Timatex Salatiga. This type of research used in this research is quantitative research. The number of samples used was 100 respondents. The sampling technique used random sampling. The analytical method used is the instrument test (validity and reliability), descriptive analysis test, regression test and path analysis with the SPSS version 23 program. Data collection methods are by means of interviews, observations and questionnaires. The results of this study indicate that job satisfaction and personality have a positive and significant effect on organizational commitment. Job satisfaction and personality have a positive and significant effect on organizational citizenship behavior. Organizational commitment is able to mediate the relationship between job satisfaction and personality on organizational citizenship behavior. Suggestions from this research are that company management needs to reinforce rules and give verbal sanctions to gradual warning letters to employees who are often late, also applies to employees who leave work before the due time.